Predictive Factors of Final Height in Congenital Growth Hormone Deficiency among Tunisian Children - Jemel, Manel; Guich, Dorra El; Chiboub, Maroua; Gharbi, Radhouane; Kandara, Hajer; Kammoun, Ines (Medical Science: Recent Advances and Applications Vol. 2, 2025)
Growth hormone (GH) deficiency is becoming increasingly common, necessitating early and standardized management. This study aims to analyze the clinical and paraclinical profiles of patients with GH deficiency, assess their statural response to treatment, and identify predictive factors for good treatment response. This is an observational, retrospective, and longitudinal study that involved children treated for growth delay due to GH deficiency and treated with growth hormone at the endocrinology department of the National Institute of Nutrition from January 1994 to December 2018. Patients were monitored every 6 months clinically through height and weight measurements, pubertal development, and hormonally based on IGF1 levels and other pituitary axis evaluations (especially thyroid function), and radiologically through bone age assessment. The main statural gain was significantly greater when IGF-1 levels were less than -2 (SD) compared to those at \(\ge\)-2 SD. The response to treatment depends on several factors and integrating them into a predictive model may allow for more personalized management of GH-deficient patients.